Special and differential treatment for developing countries in the WTO - Youssef, Hesham (South Centre GenevaCH, 1999)
Refers briefly to the conceptual and historical background with respect to special and differential treatment. Examines the special and differential treatment provisions in various WTO agreements and their implementation since the inception of the WTO. Discusses the issue of how special and differential treatment should be approached as the multilateral trading system continues to evolve.